2010
DOI: 10.4040/jkan.2010.40.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal Subcutaneous Fat Thickness Measured by Computed Tomography as an Estimate of Proper Gluteal Intramuscular Injections in Korean Adults

Abstract: Purpose:To study the thickness of gluteal subcutaneous fat (SCF) and propose an adequate length for needle for gluteal intramuscular injections based on computed tomography (CT) measurements. Methods: The thickness of gluteal SCF were measured and studied for 568 patients who visited a tertiary hospital in Seoul, Korea between January 2007 and February 2009 for routine health screening and who had abdominopelvic CT. Results: The average thickness of gluteal SCF was 15.92±4.08 mm in males and 24.90±5.47 mm in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Here, we showed that, within a certain range, the subcutaneous fat thickness increased by 0.63 and 0.52 mm in the abdomen and upper arm, respectively, per 1 kg/m 2 increase in BMI, which is consistent to the data from Gibney et al [3] who showed that the thickness increased by 0.4 mm per 1 kg/m 2 increase in BMI, as well as the data from Joo and Sohng [4] who reported that the thickness increased by 0.71 and 0.62 mm in males and females, respectively, per 1 kg/m 2 increase in BMI. As expected, the immediate relevance of BMI and subcutaneous fat thickness was very high like the many other domestically conducted studies [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Here, we showed that, within a certain range, the subcutaneous fat thickness increased by 0.63 and 0.52 mm in the abdomen and upper arm, respectively, per 1 kg/m 2 increase in BMI, which is consistent to the data from Gibney et al [3] who showed that the thickness increased by 0.4 mm per 1 kg/m 2 increase in BMI, as well as the data from Joo and Sohng [4] who reported that the thickness increased by 0.71 and 0.62 mm in males and females, respectively, per 1 kg/m 2 increase in BMI. As expected, the immediate relevance of BMI and subcutaneous fat thickness was very high like the many other domestically conducted studies [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…As for insulin injections, an intramuscular injection leads to a faster absorption than the desirable rate, while intradermal injection causes insulin leakage and pain, for which reasons insulin must be injected not into the muscles, dermis, and nerves, but into the subcutaneous tissue [1]. However the subcutaneous tissue thickness of patients varies depending on the age, gender, body mass index (BMI), and parts of the body [2,3], and the injected subcutaneous area depends on the length of a needle [4]. Therefore, before an insulin injection, the injection site, the subcutaneous fat thickness, the injection method, the length of the needle, and other psychological factors must be considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of skin and SCT thicknesses in other Asian populations, such as Filipinos [12], Koreans [13], and Indians [14], yielded comparable results to those obtained for the Chinese population, whereas non-Asian populations had considerably higher BMIs in a major ultrasound-based study [16, 17]. …”
Section: Commentarymentioning
confidence: 89%